Evaluation of factors related to th1-th2 immunomodulation in ovine co-infection with Corynebacterium pseudotuberculosis and Haemonchus contortus (Research, Society and Development, 2024)
Caseous lymphadenitis (CL), whose agent Corynebacterium pseudotuberculosis is responsible for developing an infectious process in sheep and goats, with consequent economic losses to the production chain. The Northeastern states have the highest number of prevalence cases, due to having the largest herds of small ruminants in the country. As with the bacterial infection of CL, parasites, such as that caused by Haemonchus contortus, also generate economic losses in sheep farming. MicroRNAs (miRNAs) have emerged as important regulatory molecules of the immune system. Some miRNAs produced during infection by intracellular pathogens such as Mycobacterium tuberculosis, for example, can negatively regulate the production of cytokines such as interferon-γ, thus increasing the pathogen's resistance to defense mechanisms. To evaluate serum levels of miRNAs and correlate with the Th1 response in sheep experimentally infected with C. pseudotuberculosis and its co-infection with the helminth H. contortus, an experimental study was carried out with fourteen sheep divided into three groups: control, infected and co-infected, where a serological test for LC, IFN-γ assay and quantification of microRNAs were carried out. Stool samples were performed with stool cultures and fecal parasitology (OPG). In the group of co-infected animals, an increase in IgG antibody titers was observed, and IFN-γ remained lower in the infected and co-infected groups when compared to the control group, thus demonstrating a possible modulation of the immune response by microRNAs expressed in these groups, indicating that a modulation of the immunological response occurs.